Dari Tiket ke Solusi: Transformasi UI/UX dalam Sistem Helpdesk Menggunakan Metode Double Diamond - Bambang Bima Nugraha; Muhammad Gilland Taffy Shafa Sheehan; Nur Ifant Ristanto; Salsa Bila; Fajar Mahardika (INFOKABIN (Informatika Komputasi Aplikasi dan Bisnis), 2026)
The helpdesk system is an essential component in supporting user services; however, several issues are still frequently encountered, such as a less intuitive interface, complex ticket reporting workflows, and low user satisfaction levels. This study aims to transform the UI/UX design of the helpdesk system in order to improve efficiency, effectiveness, and user experience. The method used in this study is the Double Diamond method, which consists of four stages: Discover, Define, Develop, and Deliver. This study involved 50 respondents, consisting of system users and administrators. Data collection was conducted through observation, interviews, and usability testing before and after the redesign. The results show a significant improvement after the implementation of the new design. The average ticket creation time decreased from 4.5 minutes to 2.1 minutes (an efficiency increase of 53%), the task success rate increased from 68% to 90%, and the error rate decreased from 25% to 10%. In addition, the user satisfaction score increased from 2.8 to 4.2 (on a 1–5 scale), and the System Usability Scale (SUS) score improved from 58 (poor category) to 82 (good category). The findings indicate that the application of the Double Diamond method is effective in producing a more user-friendly and efficient UI/UX design, as well as significantly improving user satisfaction. Improvements in navigation structure and ticket reporting workflows also have a positive impact on the overall performance of the helpdesk system.